1983
DOI: 10.1136/thx.38.4.297
|View full text |Cite
|
Sign up to set email alerts
|

Dose-response comparison of ipratropium bromide from a metered-dose inhaler and by jet nebulisation.

Abstract: The dose-response relationships of the anticholinergic bronchodilator drug ipratropium bromide were studied. Cumulative doses totalling 288

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

1987
1987
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 11 publications
0
3
0
2
Order By: Relevance
“…Using measurements of large airways flow we have demonstrated that vagal activity to the bronchi can be blocked completely using intravenous atropine but not by nebulized ipratropium. A single large dose of ipratropium was used based on previous literature so as to keep the methodology of the study as simple as possible (Gomm et al, 1983;Jenkins et al, 1982). This dose would almost certainly block completely airway muscarinic receptors both at 04.00 h and 16.00 h (Catterall et al, 1988).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using measurements of large airways flow we have demonstrated that vagal activity to the bronchi can be blocked completely using intravenous atropine but not by nebulized ipratropium. A single large dose of ipratropium was used based on previous literature so as to keep the methodology of the study as simple as possible (Gomm et al, 1983;Jenkins et al, 1982). This dose would almost certainly block completely airway muscarinic receptors both at 04.00 h and 16.00 h (Catterall et al, 1988).…”
Section: Resultsmentioning
confidence: 99%
“…Before the subjects received either the active or the placebo arm, three sets of baseline measurements were performed separated by 10 min intervals. Peak expiratory flow rate (PEFR), specific airways conductance (sGaw) and pulse rate were measured 5 min after each intravenous injection and 1 h after nebulisation (Gomm et al, 1983;Jenkins, 1982). The best of three PEFRs and the average of sixteen panting loops for sGaw were used at each stage of the experiment except for the runin period when the best of nine PEFRs and the average of 48 panting loops were used.…”
Section: Methodsmentioning
confidence: 99%
“…Авторы провели сравнительное исследование применения небулизационного раствора и ДАИ ипратропия бромида у пациентов преимущественно с бронхиальной астмой и установили, какая доза препарата необходима для получения 99% максимально достижимого бронходилататорного ответа на ипратропии. Для раствора, распыляемого при помощи небулайзера Wright, эта доза составляла 78 мкг и 82 мкг, когда применялся ДАИ [33].…”
Section: влияние различных средств доставки препаратов на клиническую эффективность бронходилататоровunclassified
“…[53][54][55] Twenty three studies in adults showed clinical equivalence for inhaler devices and nebulisers for the main pulmonary outcomes (FEV 1 and PEFR) and no evidence of significant difference in other outcomes. [56][57][58][59][60][61][62][63][64][65][66][67][68][69] Figure 5 shows the standardised mean difference of FEV 1 between nebulisers and hand held inhaler devices for the delivery of β agonists in stable asthma. 54 57-60 62 63 65-67 69-71 Updated searching identified two further studies.…”
Section: Effectiveness Of Nebulisersmentioning
confidence: 99%